Anthraquinones from Morinda citrifolia Roots - Ee, G.C.L.; Wen, Y.P.; Sukari, M.A.; Go, R. (Asian Journal of Chemistry, 2010)
Following our finding of 2-ethoxy-1-hydroxyanthraquinone (1) from Morinda citrifolia root, we further investigated the same part of this plant and it gave us 2-(ethoxy-ethyl)-1- hydroxyanthraquinone (2). Along with these new compounds, five other known anthraquinones, 1-hydroxy-2-methylanthraquinone (3), damnacanthal (4), nordamnacanthal (5), 2-formyl-1- hydroxyanthraquinone (6) and morindone-6-methyl-ether (7) were also isolated from the same plant. The structures of these compounds were elucidated based on spectroscopic analysis such as NMR, MS and IR.